2018
DOI: 10.1002/prp2.397
|View full text |Cite
|
Sign up to set email alerts
|

Direct and cytokine‐mediated effects of albumin‐fused growth hormone, TV‐1106, on CYP enzyme expression in human hepatocytes in vitro

Abstract: Some biologics can modulate cytokines that may lead to changes in expression of drug‐metabolizing enzymes and cause drug‐drug interactions (DDI). DDI potential of TV‐1106—an albumin‐fused growth hormone (GH)—was investigated. In this study, human blood was exposed to recombinant human growth hormone (rhGH) or TV‐1106, followed by isolation of the plasma and its application to human hepatocytes. While the treatment of blood with rhGH increased multiple cytokines, treatment of blood with TV‐1106 had no effect on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
(45 reference statements)
0
5
0
Order By: Relevance
“…The in vitro effect of IL‐6 on the mRNA expression of CYP enzymes in primary human hepatocytes have been reported in multiple studies 25‐43 . IL‐6 substantially downregulates the mRNA expression of CYP3A4 up to 100‐fold at 10 ng/mL, 26–28,30–32,34–43 whereas other CYP enzymes are downregulated 1.5‐ to 8‐fold by 10 ng/mL IL‐6 26–28,31,34,35,37–43 .…”
Section: Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…The in vitro effect of IL‐6 on the mRNA expression of CYP enzymes in primary human hepatocytes have been reported in multiple studies 25‐43 . IL‐6 substantially downregulates the mRNA expression of CYP3A4 up to 100‐fold at 10 ng/mL, 26–28,30–32,34–43 whereas other CYP enzymes are downregulated 1.5‐ to 8‐fold by 10 ng/mL IL‐6 26–28,31,34,35,37–43 .…”
Section: Resultsmentioning
confidence: 97%
“…[25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] IL-6 substantially downregulates the mRNA expression of CYP3A4 up to 100-fold at 10 ng/mL, [26][27][28][30][31][32][34][35][36][37][38][39][40][41][42][43] whereas other CYP enzymes are downregulated 1.5-to 8-fold by 10 ng/mL IL-6. [26][27][28]31,34,35,[37][38][39][40][41][42][43] A study reported a 2-fold upregulation of CYP2D6 mRNA by IL-6, 34 however, two other studies reported a maximum of 2to 3-fold downregulation of CYP2D6 mRNA at the same IL-6 concentration.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations